Complete Genome of Ignavibacterium album, a Metabolically Versatile, Flagellated, Facultative Anaerobe from the Phylum Chlorobi - Liu, Zhenfeng; Frigaard, Niels-Ulrik; Vogl, Kajetan; Iino, Takao; Ohkuma, Moriya; Overmann, Joerg; Bryant, Donald A. (Frontiers in Microbiology, 2012)
Prior to the recent discovery of Ignavibacterium album (I. album), anaerobic photoautotrophic green sulfur bacteria (GSB) were the only cultivated members of the bacterial phylum Chlorobi. In contrast to GSB, sequence analysis of the 3.7-Mbp genome of I. album shows that this recently described member of the phylum Chlorobi is a chemoheterotroph with a versatile metabolism. I. album lacks genes for photosynthesis and sulfur oxidation but has a full set of genes for flagella and chemotaxis. The occurrence of genes for multiple electron transfer complexes suggests that I. album is capable of organoheterotrophy under both oxic and anoxic conditions. The occurrence of genes encoding enzymes for CO2 fixation as well as other enzymes of the reductive TCA cycle suggests that mixotrophy may be possible under certain growth conditions. However, known biosynthetic pathways for several amino acids are incomplete; this suggests that I. album is dependent upon on exogenous sources of these metabolites or employs novel biosynthetic pathways. Comparisons of I. album and other members of the phylum Chlorobi suggest that the physiology of the ancestors of this phylum might have been quite different from that of modern GSB.